Professional Autonomy as Centrality in Best Practices in Nursing - Maria Angélica de Almeida Peres; Lygia Paim; Marcos Antonio Gomes Brandão (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to reflect on professional, user and family autonomy as a centrality in Best Practices in nursing in Brazil. Methods: this is a theoretical-reflective study. Results: from a retrospective look at the creation and evolution of nursing autonomy in its knowledge and care practices, it exposes the use of autonomy in nursing care and foster the participation of the user and his family as the center of Best Practices in nursing. Final considerations: the text suggests the institutional commitment of health services to the formal postgraduate education of nurses and the prospect of more autonomy and quality for the expression of Best Practices in nursing.